Pelembagaan Hukum Islam Untuk Masa Depan Bangsa Indonesia yang Pluralistik - Ni’matul Huda (Unisia, 2007)
Choosing either formalism or cultural models in the institutionalization of Islamic Law in the context of the United State of Republic of Indonesia has not been too easy, and this has even frequently been harsh discourses between both proponents. Therefore, the proponents should first of all seek their common view on the concept, process, and legal and political consequence of such institutionalization. The institutionalization of Islamic Law should not only seek legal-its values for the development, order, security and welfare of the people and state. Keywords: Cultural, formal, institutionalization, Islamic Law, model.